PATU10 Neuromyelitis optica and related spectrum disorders in a UK population-based sample. Issue 11 (22nd October 2010) - Tackley, G; Burtonwood, M T; Ingram, G; Cossburn, M D; Malik, G A; Pickersgill, T; Robertson, N P
Abstract : Neuromyelitis Optica (NMO) is a rare neuroinflammatory disorder with limited epidemiological data. Antibodies against aquaporin-4 (Aq4ab) are reported to be highly specific for NMO and NMO spectrum disorders (NMO-SD). In this study we determine the prevalence of these disorders and spectrum of clinical phenotype in a population-based sample and analyse clinical features that predict Aq4ab positivity. Cases were identified from the SE Wales neuroinflammatory database and regional requests for Aquaporin-4 testing. 10 patients (M2:8, age range 7–70) with NMO were identified of which 7 had positive Aq4ab, as well as two female patients with Aq4ab positive NMO-SD; a combined prevalence of 16/million (95% CI 10 to 25). Median disease duration was 4 years (range 1–34) and median relapse frequency 0.63/year (0.14–1.60). Median MS severity score (MSSS) was 8.10 (4.35–9.59) One third of cases had severe visual impairment. MSSS did not differ between those treated with immunosuppressants (5/12) and those not. Both NMO-SD cases had isolated longitudinally extensive transverse myelitis (LETM). Aq-4ab were positive in 9/79 (11.4%) sample requests. Test requests were most commonly associated with poorly recovered optic neuritis (56.6%). Logistic regression identified the presence of LETM on MR as the most predictive feature for NMO (Likelihood ratio=5.43). In this study we have established disease prevalence for NMO in a UK population-based sample and identified LETM as the main indication for Aq4ab testing.